The predictive role of haematological parameters in the diagnosis of osteoarticular brucellosis - Balin, Safak Ozer; Tartar, Ayse Sagmak; Akbulut, Ayhan (Makerere Univ, Fac Med, 2018)
Background: Brucellosis is a zoonosis that affects several systems, especially with the osteoarticular involvement. Objectives: This study aims to compare the neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), monocyte/lymphocyte ratio (MLR), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), mean platelet volume (MPY) and red blood cell distribution (RDW) in patients with the osteoarticular involvement and those with non-localised brucellosis and evaluate their predictive value for the diagnosis of osteoarticular brucellosis. Methods: We enrolled 140 patients with brucellosis, 70 with the osteoarticular involvement and 70 without any localised involvement. We collected patients' data retrospectively and compared haematological parameters between both groups. In patients with osteoarticular brucellosis, a correlation of the NLR with the ESR and CRP and correlation of the MLR with the ESR and CRP were assessed. Furthermore, the predictive performance of the ESR, CRP, NLR and MLR on the osteoarticular involvement was evaluated. Results: The NLR, MLR, ESR, CRP, neutrophil and monocyte levels were higher in the patient group than the control group. Conclusion: The NLR, MLR, ESR and CRP are useful parameters to estimate the clinical course of patients with brucellosis, and the NLR and MLR are alternative to inflammatory markers in the osteoarticular involvement.
Keywords: Neutrophil/lymphocyte ratio; monocyte/lymphocyte ratio; inflammatory marker